Second Language : Poems - Mueller, Lisel (Book collections on Project MUSE., 1986)
Second Language is the fourth volume of work from the highly acclaimed poet Lisel Mueller. The second language of the title, English, supplanted Mueller's native language when she came to the United States from Hitler's Germany at age fifteen. But other second languages are at work here as well. The poems in this collection have to do with memory and metaphor, two forces that enable us to interpret our experience. Each is in a sense a second language, and in Mueller's employ each gains expression in an imaginative and humanistic voice. In "English as a Second Language," the various meanings of Second Language come together lucidly and effectively.